Sustainability of Maine’s Emerging Wine Industry - Murray, Michaela; Haggerty, Mark; Welcomer, Stephanie (Maine Policy Review, 2020)
Consumers, businesses and business sectors, and policymakers are increasingly concerned with sustainability, and the global wine industry has long acknowledged concerns about the social, environmental, and economic sustainability of their industry. Several wine regions, including France, Australia, and South Africa, have developed workbooks and policies for sustainable wine production, but Maine’s emerging wine industry has yet to explore the concept of sustainability as it relates to its operations. In this project, designed in collaboration with the Maine Winery Guild, we interviewed the owners of 10 Maine wineries and analyzed how they define and enact sustainability along with the obstacles they face in sustainability efforts. This research aims to provide baseline information that will help the guild and policymakers formulate actions that enable Maine’s wine industry to grow and compete with other sustainability-conscious wine regions.
Keywords: triple bottom line; social sustainability; environmental sustainability; economic sustainability; fruit wine